Packing density of ternary cementitious particles based on wet packing method - Chu, Shaohua (2023)
The particle packing of cementitious materials is of essential importance to the performance of paste which constitutes the most uncertain part of mortar/concrete. Such importance is arising from the fact that the design of cementitious particle system inevitably involves the packing design, particularly for the emerging materials of 3D printable concrete and ultra-high performance concrete (UHPC). So far, scientific understanding of the particle packing in these emerging materials remains inadequate. In this regard, wet packing method (WPM) was used to measure the wet packing density (WPD) of ternary particle systems consisting of cement, pulverized fuel ash (PFA) and micro-silica (MS). The optimum ternary particle system in terms of WPD was determined. Comparison between the experimental results and Andreasen and Andersen (A&A) model revealed the limitations of A&A model. The design approach based on WPD contour shall advance particle packing-oriented cement and concrete science towards sustainable concrete design.